Impact Features of Water Source Mining on Spring Groups in Jinan City. Issue 3 (May 2020) - Wu, Dongqiang; Xing, Liting; Zhao, Zhenhua; Yao, Chunmei; Li, Jiangbai; Yu, Miao; Meng, Qinghan
Abstract: In order to protect Jinan spring. This article is based on the research and analysis of the observation water level, extraction volume, spring water level, and observation data of water sources in West Jinan, western suburbs, and urban areas. It is concluded that: (1) According to the analysis of the dynamic type of groundwater level, there is a close hydraulic connection between the groundwater of West Jinan and Baotu spring spring group, which is a unified body of water with strong connectivity. (2) From the analysis of multi-year water level, spring discharge and mining volume, the impact of karst water mining in the western suburbs on the water level and spring discharge of urban spring water is very obvious.(3) The increase in the amount of karst water in the urban area and the decrease in the flow of spring water are very similar. Therefore, Jinan spring water is obviously affected by artificial mining. Controlling the amount of groundwater extraction, especially in urban areas, is of great significance to ensure the spring water gushing all year round. At the same time, it is necessary to make a good mining layout for the water sources in the western suburbs, West Jinan and eastern suburbs.